2023
DOI: 10.1039/d3nr00984j
|View full text |Cite
|
Sign up to set email alerts
|

Effective modulation of the exotic properties of two-dimensional multifunctional TM2@g-C4N3 monolayers via transition metal permutation and biaxial strain

Abstract: The exotic physicochemical properties of TM atoms (3d, 4d, and 5d) embedded g-C4N3 as a novel class of 2D monolayers were systematically investigated through hierarchical high-throughput screening combined with spin-polarized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The magnetic anisotropy energy (MAE) is an important parameter of magnetic materials to determine the low-temperature magnetic orientation, which is directly related to the thermal stability of magnetic data storage . Our calculations including the spin–orbital coupling effect demonstrated that 2D T-MoS 2 F 2 has in-plane magnetic anisotropy with the easy magnetization axis parallel to the x direction (100), and the MAE is 804 μeV/Mo, which is comparable to or even higher than that of typical 2D magnets, such as CrX 3 (X = Cl, Br, and I) monolayers (25, 160, 804 μeV/Cr), CrXTe 3 (X = Si, Ge, and Sn) monolayers (419, 220, 69 μeV/Cr), and the Fe 3 GeTe 2 monolayer (920 μeV/Fe) as well as TM atoms (TM = Zr, Ru, Rh, and Pt) embedded g -C 4 N 3 (∼600–1100 μeV/TM) …”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The magnetic anisotropy energy (MAE) is an important parameter of magnetic materials to determine the low-temperature magnetic orientation, which is directly related to the thermal stability of magnetic data storage . Our calculations including the spin–orbital coupling effect demonstrated that 2D T-MoS 2 F 2 has in-plane magnetic anisotropy with the easy magnetization axis parallel to the x direction (100), and the MAE is 804 μeV/Mo, which is comparable to or even higher than that of typical 2D magnets, such as CrX 3 (X = Cl, Br, and I) monolayers (25, 160, 804 μeV/Cr), CrXTe 3 (X = Si, Ge, and Sn) monolayers (419, 220, 69 μeV/Cr), and the Fe 3 GeTe 2 monolayer (920 μeV/Fe) as well as TM atoms (TM = Zr, Ru, Rh, and Pt) embedded g -C 4 N 3 (∼600–1100 μeV/TM) …”
mentioning
confidence: 80%
“…59 Our calculations including the spin−orbital coupling effect demonstrated that 2D T-MoS 2 F 2 has in-plane magnetic anisotropy with the easy magnetization axis parallel to the x direction (100), and the MAE is 804 μeV/Mo, which is comparable to or even higher than that of typical 2D magnets, such as CrX 3 (X = Cl, Br, and I) monolayers (25, 160, 804 μeV/Cr), 60 CrXTe 3 (X = Si, Ge, and Sn) monolayers (419, 220, 69 μeV/Cr), 61 and the Fe 3 GeTe 2 monolayer (920 μeV/Fe) 62 as well as TM atoms (TM = Zr, Ru, Rh, and Pt) embedded g-C 4 N 3 (∼600−1100 μeV/TM). 63 T C is a key parameter for the practical application of spintronic devices. Previous works have shown that Monte Carlo (MC) simulation based on the Heisenberg model is a reliable method to estimate the Curie temperature of 2D magnetic materials.…”
mentioning
confidence: 99%
“…Notably, with the development of theoretical computational chemistry, theoretical calculation of the electrocatalytic NRR has attracted much attention, which proposed several high-activity catalysts and possible reaction processes. For example, by means of DFT, a wide range of TM atoms have been anchored on various 2D nanomaterials, including graphene and nitrogen doped derivatives, 51–54 defective Fe 3 GeTe 2 monolayers, 55,56 MBene monolayers, 57 transition metal borides, 58,59 graphdiyne (GDY), 45,60 MoS 2 , 32 boron nitride (BN) 35 and ZnO monolayers, 61 which can be considered as highly efficient electrocatalysts for the NRR. Therefore, heteroatom doping to adjust the interaction between supports and heteroatoms can improve the catalytic activity of SACs for the NRR.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) nanomaterials have attracted intense interest because of their unique chemical, mechanical, optical, and electrical properties. [28][29][30][31] MXenes are two-dimensional transition metal carbides, carbonitrides, and nitrides with the general formula M n+1 X n T x , where M is an early transition metal (such as Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, and Mo), X is carbon and/or nitrogen, and Ti stands for surface terminations (H, O, or F). [32][33][34] MXenes are now being used in thermal catalysis due to their adaptable surface terminations and strong thermal endurance.…”
Section: Introductionmentioning
confidence: 99%